2006
DOI: 10.1074/jbc.m608580200
|View full text |Cite
|
Sign up to set email alerts
|

Specific Adduction of Plant Lipid Transfer Protein by an Allene Oxide Generated by 9-Lipoxygenase and Allene Oxide Synthase

Abstract: Lipid transfer proteins (LTPs) are ubiquitous plant lipidbinding proteins that have been associated with multiple developmental and stress responses. Although LTPs typically bind fatty acids and fatty acid derivatives in a non-covalent way, studies on the LTPs of barley seeds have identified an abundantly occurring covalently modified form, LTP1b, the lipid ligand of which has resisted clarification. In the present study, this adduct was identified as the ␣-ketol 9-hydroxy-10-oxo-12(Z)-octadecenoic acid. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 53 publications
5
43
1
Order By: Relevance
“…Several of the down-regulated genes encode lipid transfer proteins (AtLTP3, At5g59320; AtLTP4, At5g59310; AtLTP6, At3g08770; AtLTP12, At3g51590). LTPs are ubiquitous plant lipid-binding proteins proposed to function in various developmental and stress responses, signaling, and cell wall loosening (Kader, 1996;Bakan et al, 2006;Yeats and Rose, 2008). Furthermore, expression of the cell wall-loosening gene AtEXPB3 (At4g28250; encoding expansin) and the xyloglucan endotransglucosylase/ hydrolase genes AtXTH9 (At4g03210) and AtXTH19 (At4g30290) was markedly reduced upon EBE induction.…”
Section: Ebe-triggered Changes In Gene Expressionmentioning
confidence: 99%
“…Several of the down-regulated genes encode lipid transfer proteins (AtLTP3, At5g59320; AtLTP4, At5g59310; AtLTP6, At3g08770; AtLTP12, At3g51590). LTPs are ubiquitous plant lipid-binding proteins proposed to function in various developmental and stress responses, signaling, and cell wall loosening (Kader, 1996;Bakan et al, 2006;Yeats and Rose, 2008). Furthermore, expression of the cell wall-loosening gene AtEXPB3 (At4g28250; encoding expansin) and the xyloglucan endotransglucosylase/ hydrolase genes AtXTH9 (At4g03210) and AtXTH19 (At4g30290) was markedly reduced upon EBE induction.…”
Section: Ebe-triggered Changes In Gene Expressionmentioning
confidence: 99%
“…Bakan et al (2006) demonstrated that the LTP1b consisted of an allene oxide that is specifically adducted to barley LTP1 at Asp7 by the action of 9-lipoxygenase and allene oxide synthase. The similarity of the adduct structure to precursors of jasmonic acid suggests a role in signaling, although a role in trapping of toxic oxylipins may also be possible.…”
Section: Ltps and Defense Against Pathogensmentioning
confidence: 99%
“…Another form of LTP, named LTP1b, corresponds to LTP1 with a covalently linked lipid-like molecule of mass 294 Da, esterically bound to an aspartate residue. The lipid adduct was identified as 9,10-dihydroxy-12(Z)-octadecenoic acid 1 . The major MS signals representing the molecular masses in the range m/z 9,986 ± 4 Da correspond to LTP1b.…”
Section: Resultsmentioning
confidence: 99%